Использование методологии историко-научных исследований для изучения современной научной картины мира - Литвинко, А. С. (НТУ "ХПИ", 2013)
В статье показана значимость на современном этапе историко-научных исследований, которые формируют синтез всех областей знания, прежде всего естественно-научной и гуманитарной. Проанализирована глубокая связь научных картин мира и историко-научных исследований, предметом которых является изучение этапов формирования современной научной мысли, обобщаемых в НКМ.

In the article the importance of the historical-scientific research that forms the synthesis of all spheres of scientific knowledge, first of all natural and social sciences, is shown. A deep connection of the scientific picture of the world and historical-scientific research, the subject of which is the study of the modern scientific thought stages, summarized in the scientific picture of the world, is analyzed.
Keywords: мировоззрение; история науки; история техники; мысль научная; historical-scientific researches; science; scientific world view; history of science; history of technique